A business concept study for Macau's historic centre revitalization (The renovation of the central hotel as as example) - Cruz Vaz Pimentel, Mariana (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business valuation of Ford company - Zhang, An Qi (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A cultura nas abordagens comunicativas: análise de materiais didáticos em manuais de Português como língua estrangeira - Morais, David (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A discussion on the group psychotherapy treatment for depressed individuals - Chan, Ka Chon (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A financial valuation of Lenovo group limited - Sin, Si Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Starbucks corporation - Ho, Chon In (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation of Yahoo! Inc - Hong, Nga Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Heart Rate Variability-based Smart Approach to Analyze Frailty in Older Adults - Paulo do Vale Madeiro, João; César Cortez, Arnaldo Aires Peixoto Júnior, Paulo; Alexandre Lôbo Marques, João; Alisson Pessoa Guimarães, Antônio; Hebert da Silva Felix, John (The Smart Computing Review, 2015)
This paper presents an algorithm that applies metrics derived from automatic QRS detection and segmentation in electrocardiogram signals for analyzing Heart Rate Variability to study the evolution of metrics in the frequency domain of a clinical procedure. The analysis was performed on three sets of elderly people, who are categorized according to frailty phenotype. The first set was comprised of frail elderly, the second pre-frail elderly, and the third robust elderly. Investigators from many disciplines have been encouraged to contribute to the understanding of molecular and physiological changes in multiple systems that may increase the vulnerability of frail elderly. In this work, the frailty phenotype can be characterized by unintentional weight loss, as self-reported, fatigue assessed by self-report, grip strength (measured directly), physical activity level assessed by self-report and gait speed (measured). The results obtained demonstrate the existence of significant differences between Heart Rate Variability metrics for the three groups, especially considering a higher preponderance for sympathetic nervous system for the group of robust patients in response to postural maneuver.

A receção da figura de Melquisedeque na literatura cristã latina - Eleutério, JM (Didaskalia, 2015)
A interpretação da Escritura e das suas diferentes personagens enriquece a Tradição cristã, mas este processo de receção é muitas vezes marcado por debates e polémica …

A review of the Colloquium «Narrative, Media and Cognition» — a cartography of the borders of narrative - Castro, Maria Guilhermina; Caires, Carlos Sena; Ribas, Daniel; Palinhos, Jorge (Journal of Science and Technology of the Arts, 2015)
We present an overview and discussion of the Colloquium «Narrative, Media and Cognition», which took place at Porto's Centre of Catholic University of Portugal in July of 2015, under the organization of the Research Centre for Science and Technology of the Arts (CITAR). Several scholars of different areas presented research about the uses and advances in narrative study and practice in a broad range of areas, giving some important insights about the latest developments in Narrative Studies, Ontology of Narrative and the uses of Narrative in Art, Cinema, Performance, Journalism, Marketing and Literature, among other fields. After briefly describing the main points of each presentation in the Colloquium we try to draw some conclusions and possibilities raised by the Colloquium and take a glimpse of future paths that the use of Narrative can end up taking.

A Review of the Macau's Judiciary Police: Opportunities and Challenges in the Wake of the 21st Century - Che, Ion Fong (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A study on optimizing the heritage interpretation system in Macao S.A.R - Wong, Cheng Man (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

An Educological Analysis of Multisensory Instruction for Teaching Chinese: A Case Study Of Macao - Found, Andrew; Hwee, Chia Kok (University of Saint Joseph, 2015)
Keywords: China Macau (Special Administrative Region); Chinese language; Study and teaching

An insight on University of Saint Joseph strategic management as part of Macao lifelong learning education system - Lam, Pui Ieng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Are the devotions of the Passion of Jesus in Macao still a "Dangerous memory"? - Eleutério, João Marques (Asian Conference on Ethics, Religion & Philosophy, 2015)
Among the multiple images used to promote Macao as a touristic destination, we can find some related with the Christian traditions, in particular with the Catholic devotions to the Passion of Christ and the cult of the Virgin Mary. Discussing the concept of “dangerous memory” as proposed by Johann Baptist Metz and analyzing the rituals associated with the devotions around the Passion of Jesus, this paper aims to look at, and present, the different perceptions of a message of subversion of unbalanced relations of power and domination, such as the image of the suffering Jesus in the contemporary society of Macau. The method followed in this paper is ethnographic and structured around some major contributions in the field of Ritual Studies. The implications of this research are related with the different perceptions and usages of a religious image and the drift of its power.

As fronteiras do sentido num projeto educacional europeu:uma grounded theory - Lopes, Carlos Manuel de Brito Mariano de Vasconcelos (University of Saint Joseph, 2015)
Esta dissertação reporta uma investigação realizada com o objectivo de se compreender a persistente dificuldade de integração sentida no patamar transnacional de um projeto educacional europeu Comenius, de parceria entre escolas. A Grounded Theory foi a metodologia selecionada para orientar a recolha e análise de dados. Os dados empíricos primários foram extraídos de entrevistas abertas, não estruturadas, realizadas aos professores europeus envolvidos nas atividades do projeto. Identificou-se, como principal fator obstrutivo da unidade operacional a esse nível no projeto, a existência de significativas barreiras à comunicação entre os diferentes parceiros europeus, latentes, pouco compreensíveis, mas extraordinariamente operativas. Implicações do estudo e sugestões para esforços subsequentes visando evitar ou, pelo menos, contornar o mesmo tipo de problema, ou problemas similares, estão incluídas
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Attitudes and self-beliefs of ability towards mathematics and science and their effects on career choices A case study with Macao-chinese girls - Correia, Ana; Fernandes, Clara; Maia, Joao (Third International Conference on Advances In Economics, Social Science and Human Behaviour Study - ESSHBS 2015, 2015)
This study explores girls’ attitudes and selfassessment of abilities towards mathematics and science and its effects on career preferences. Results from Pi

Barometer of Business Relations between China and Portuguese Speaking Countries: An Economic, Commerical and Cultural Approach - Rato, Ricardo (University of Saint Joseph, 2015)

Birth date predicts alternative life‐history pathways in a fish with sequential reproductive tactics - Fagundes, Teresa; Simões, Mariana G.; Saraiva, João L.; Ros, Albert F. H.; Gonçalves, David; Oliveira, Rui F. (Functional Ecology, 2015)

Bowler plus: bowling ball feedback device - Leong, Chou Kin (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Bringing Life Science to Primary and Secondary School Students in Macao: From Genes to Environment - Tagulao, Karen (University of Saint Joseph, 2015)

Business plan for a nursery education school - Wong, Weng Ian (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Catholic Orders as Efficient Institutions - Rothlin, Stephan; Frey, B. S (Lumen: A Journal of Catholic Studies, 2015)

Conception of a southern Portuguese wine: a fesibility analysis - Santos, João (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Conceptual frameworks of big data generation for Macao - Sousa, Ana Paula Soares Batalha da Silva de (University of Saint Joseph, 2015)
Keywords: Big data; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.

Connectivism and the Use of Technology/Media in Collaborative Teaching and Learning - Thota, Neena (New Directions for Teaching and Learning, 2015)
This chapter explores the ways in which a relational understanding of the education process and the use of collaborative technologies in the connectivist tradition might inform and transform university teaching.

Contemplation on Today’s Digital Education - Negreiros, João; de Fatima Oliveira, Maria (Springer International Publishing, 2015)
This paper starts to address the affect and side-effects of social media on people’s live in a pure contemplation perspective. Social networks are revised and some issues regarding its impact on education was not forgotten such as the teacher role in the digital classroom, formal versus informal learning or Web 2.0 tools use. Since Moodle is the first Learning Management System whilst Facebook is the first social network in the world, a survey was accomplished with two independent classes of e-business students at University of Saint Joseph, Macao, China, on their attitudes toward both online services in a learning framework. In general, the results confirms to a certain extent others previous studies on the question of whether using Facebook as an educational tool is more effective than Moodle.
Keywords: Education; Facebook; Macao; Moodle; Social Networks

Coping with Merging and Advanced Market Risks - Xia, Harry (International Journal of Economics and Social Science, 2015)

Corporate social responsibility in Macau gaming industry - Madureira, Óscar Alberto Correia da Costa (University of Saint Joseph, 2015)
Keywords: Gambling; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Cross-Adaptive Polarity Switching Strategies for Optimization of Audio Mixes - Pestana, Pedro; Reiss, Josh; Barbosa, Alvaro (2015)

Current practices of successful Hong Kong middle school choral directors in working with voice-changing boys - Lam, Hoi Yan (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Da aptidão à aspiração: um caminho por percorrer - Correia, Ana (CECS - Publicações / eBooks, 2015)

Determinants of social media shopping intention in Macao - Ng, Iok Mui (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing Teledifusao de Macau (TDM) Issues and Prospects - Siew, Pek Leng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Diferenças étnico-culturais e expectativas académicas entre dolescentes Macaenses, Portugueses Europeus, Africanos e Chineses ultramarinos: estudo de caso em contexto escolar - Street, Maria Cristina Munhoz (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Domestic Violence in Macao: Its Socio-Cultural, Psychological and Economic Perspectives to Public Policy Making - Munoz-Agcaoili, Suzette (University of Saint Joseph, 2015)

Ear traning and the improvement intonation for the choir - Lam, Iok Teng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Educational leadership practices in East Timor Catholic schools: a case study - Gusmão, Domingos (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Engaging School Students with Tangible Devices: Pilot Project with .NET Gadgeteer - Thota, Neena; Estadieu, Gerald; Ferrao, Antonio; Meng, Wong Kai (2015 International Conference on Learning and Teaching in Computing and Engineering (LaTiCE), 2015)

English learning strategies and strategy instruction: a mixed methods study of EFL students in higher education - Chan, Mei Lan (University of Saint Joseph, 2015)
This thesis investigates the Language Learning Strategies (LLS) used by English as a Foreign Language (EFL) nursing students of higher education in Macao and the effectiveness related to students’ learning outcomes by Strategy Instruction (SI). To date there has been no literature in the area of SI among the Macao Chinese EFL higher education students on teaching all LLS groups, and on four main English skills to look at its effects on learning processes and outcomes at the same time, and this study starts to fill the gap. The research uses an embedded mixed methods research design in phase one and an embedded mixed methods quasi-experimental design in phase two. Phase one aimed to identify students’ LLS use. The findings revealed that students’ cognitive, metacognitive and compensatory strategies were used more than affective, memory-related and social strategies, and overall they used a medium to low level of LLS. In phase two, the effects of SI on students’ changes of LLS use, their proficiency and English learning processes were identified. After SI, students used LLS both more widely and frequently in all four main English skills. Most students’ motivation and self-confidence were enhanced. After SI the affective group of strategies in the treatment group statistically significantly improved, with a moderate effect size, from that of the comparison group. It was found that the widely used Strategy Inventory for Language Learning questionnaires by Oxford (1989c) had limited statistical power and some conceptual confusion. Recommendations are made for policy and practice of EFL instruction
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Environmental Urban Design and Planning Rules and their Impact on Street Spaces in Hong Kong and Macau - Tieben, Hendrik; Chu, Joanna; Soares, Nuno; Yiu, Edward (8th Conference of the International Forum on Urbanism (IFoU), 2015)

Exploratory study of management style change in Laos - Xian, Jia Xing (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study on perceptions of young adults about speed dating service in Macao - Kuong, Weng Man (University of Saint Joseph, 2015)
Keywords: Dating services; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Young adults

Exploring attitudes concerning family size in Macau: a qualitative study - Ho, Nga Si (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Feasibility study for a movie production setting in Macau - Tam, Pek Kei (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Festas e lugares da memória dos índios Potiguara – a invenção das tradições locais - Simoes, José Manuel (Tokyo University of Foreign Studies, 2015)

Financial challenges of small medium emterprises in China - Fok, Gerald (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial valuation of Campbell Soup Company - Wong, Chong Weng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Fish Sounds and Mate Choice - Amorim, M. Clara P.; Vasconcelos, Raquel O.; Fonseca, Paulo J. (Sound Communication in Fishes, 2015)
Fish acoustic signals associated with mating behaviour are typically low-frequency sounds produced by males when in close proximity to females. However, some species make sounds that serve the function and follow the design of advertisement calls, well known in insects, anurans, and birds. Close-range courtship acoustic signals may be used by females in mate assessment as they contain information of male quality such as size and condition. For example, sound-dominant frequency, amplitude, and fatigue resistance may signal body size whereas pulse period (i.e. muscle contraction rate) and calling activity are related with body condition in some species. Some signal features, such as sound pulse number, may carry multiple messages including size and condition. Playback experiments on mate choice of a restricted number of species suggest that females prefer vocal to silent males and may use sound frequency, amplitude, and mainly calling rateCalling ratewhen assessing males. The assessment of males by females becomes more challenging when males engage in choruses or when sounds are otherwise masked by anthropogenic noise but almost nothing is known about how these aspects affect mating decisions and fish reproductive success.
Keywords: Acoustic communication; Anthropogenic noise; Calling activity; Chorus; Fish; Mate choice; Reproductive success

Gastronomy as a sub-sector of the creative industries: the case study of Macau - De Sousa, Carlos Humberto (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Globalization, Communication, Information and Cohabitation - Simoes, José Manuel (8th Annual Conference of the Chinese Association of Global Communication, 2015)

Gratitude interventions: the person-activity fit dimension - Todd, Philip (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

GROKYA: a privacy-friendly framework for ubiquitous computer - Farinha, Daniel Filipe G. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

Hotel central, Macau leveraged buyout plan - Real, Sérgio Miguel Anacleto (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How to create and develop a Choir in Chinese christian church of Macau - Chao, Chou (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Impact Assessment of the Macao Forum's Seminars (colloquia) on the Economy and Public Policy-Making in Portuguese Speaking Countries - An Illustration of South-South Cooperation - Tran, Émilie (University of Saint Joseph, 2015)

Implement performanace pledge in Macao government departments: a case of Macao IACM - Choi, Kuai Hong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Influence of Chinese legitimizing discourse on domestic violence in Macau: a preliminary study - Lam, Hang U. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Introducing new ventures in Macau traditional retail - Ao, Wan Meng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Like a Tree Planted By Streams of Water :The Baptist Church Takes Root In Macao (John and Lilian Galloway 1908-1968) - Ballew, Robert Lawrence (University of Saint Joseph, 2015)
In 2014 Macao Baptist Church celebrated it’s 110th anniversary. How did the Baptist church come to be established in the Portuguese, predominantly Catholic and Buddhist city of Macao? Through careful examination of letters and reports from the main protagonists, John Laurels and Lilian Reeves Todd Galloway, the process of establishing the Baptist church can be revealed and understood within the greater context of the Baptist missionary work in China. The Galloway’s work will be evaluated through a framework of missions eras presented by Dr. Ralph D. Winter. This work looks at the material in two major sections; first, the lives of the Galloways in Macao from 1908 to 1968, and second, the missionary methods of the Galloways over the same period. Using missiological methods of the Kingdom Mission era, the Galloways stood firmly in the Church Mission era focusing their efforts on Personal rather than Social Transformation efforts. Their work laid the foundation for a century of Baptist work in Macao by local Christians as well as foreign missionaries.
Keywords: Baptists; China Macau (Special Administrative Region); China--Macau (Special Administrative Region); Christianity; Church property; Education; Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

Luxury brand development in Macau - Chio, Lai Teng (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau, Are We Ready? Challenges On Healthcare Delivery in Nursing Home Settings (QNQ Study - Phase Two) - Ho, Jacky C. K (University of Saint Joseph, 2015)

Macau as a wealth management hub for economic diversfication: a feasibilit study - Ho, Chi Hong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau comparative study with intelligent cities - Lao, Ka Fun (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau consumers' attitudes toward mobile advertising - Wong, Iok Fong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau's Strategies to Develop Training of Talented People with Expertise in the Cooperation between China and Portuguese Speaking Countries - Alves, Jose (University of Saint Joseph, 2015)

Metodologias e estratégias no ensino de vocabulário da língua Portuguesa em duas escolas secundárias de Macau - Rosário, Isabel Dillon Lei Do (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Neurogenomic mechanisms of social plasticity - Cardoso, Sara D.; Teles, Magda C.; Oliveira, Rui F. (Journal of Experimental Biology, 2015)
Skip to Next Section Group-living animals must adjust the expression of their social behaviour to changes in their social environment and to transitions between life-history stages, and this social plasticity can be seen as an adaptive trait that can be under positive selection when changes in the environment outpace the rate of genetic evolutionary change. Here, we propose a conceptual framework for understanding the neuromolecular mechanisms of social plasticity. According to this framework, social plasticity is achieved by rewiring or by biochemically switching nodes of a neural network underlying social behaviour in response to perceived social information. Therefore, at the molecular level, it depends on the social regulation of gene expression, so that different genomic and epigenetic states of this brain network correspond to different behavioural states, and the switches between states are orchestrated by signalling pathways that interface the social environment and the genotype. Different types of social plasticity can be recognized based on the observed patterns of inter- versus intra-individual occurrence, time scale and reversibility. It is proposed that these different types of social plasticity rely on different proximate mechanisms at the physiological, neural and genomic level.

O património industrial de Macau até 1999: estudo das Fábricas de Panchões - Teixeira, Vitor (Review of Culture, 2015)

Pathophysiological, cardiovascular and neuroendocrine changes in hypertensive patients during the hemodialysis session - Gutiérrez-Adrianzén, O. A.; Moraes, M. E. A.; Almeida, A. P.; Lima, J. W. O.; Marinho, M. F.; Marques, A. L.; Madeiro, J. P. V.; Nepomuceno, L.; da Silva Jr, J. M. S.; Silva Jr, G. B.; Daher, E. F.; Rodrigues Sobrinho, C. R. M. (Journal of Human Hypertension, 2015)
The pathophysiological mechanisms of arterial hypertension during hemodialysis (HD) in patients with end-stage renal disease (ESRD) are still poorly understood. The aim of this study is to investigate physiological, cardiovascular and neuroendocrine changes in patients with ESRD and its correlation with changes in blood pressure (BP) during the HD session. The present study included 21 patients with ESRD undergoing chronic HD treatment. Group A (study) consisted of patients who had BP increase and group B (control) consisted of those who had BP reduction during HD session. Echocardiograms were performed during the HD session to evaluate cardiac output (CO) and systemic vascular resistance (SVR). Before and after the HD session, blood samples were collected to measure brain natriuretic peptide (BNP), catecholamines, endothelin-1 (ET-1), nitric oxide (NO), electrolytes, hematocrit, albumin and nitrogen substances. The mean age of the studied patients was 43±4.9 years, and 54.6% were males. SVR significantly increased in group A (P<0.001). There were no differences in the values of BNP, NO, adrenalin, dopamin and noradrenalin, before and after dialysis, between the two groups. The mean value of ET-1, post HD, was 25.9 pg ml−1 in group A and 13.3 pg ml−1 in group B (P=<0.001). Patients with ESRD showed different hemodynamic patterns during the HD session, with significant BP increase in group A, caused by an increase in SVR possibly due to endothelial dysfunction, evidenced by an increase in serum ET-1 levels.
Keywords: End-stage renal disease; Haemodialysis; Hypertension

Preparatory gestures in choral-orchestral works - Ho, Cheok Ngai (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Choral Conducting (MCC); University of Saint Joseph

Re-conceptualising computer literacy teaching and learning using constructivist principles and peer-tutoring - Wong, Kin Ming (University of Saint Joseph, 2015)
Nowadays, many university students (in Macau) are required to attend computer literacy courses to develop their basic skill levels and knowledge as part of their literacy foundation requirements. To be effective, such courses, which are very staff intensive and require access to expensive equipment and software, necessitate high levels of individual teaching. Evidence gathered at two study sites during this research, strongly suggests that many students may not be benefiting sufficiently from their computer literacy courses. Teachers frequently complain about the weak IT skills of many course graduates. This research proposes an innovative model for designing and delivering computer literacy courses based on constructivist principles, using peer-tutoring and blended learning to increase cost effectiveness and to improve student outcomes. Central to the model being proposed is the training and deployment of former course graduates as peer instructors and assessors. Constructivist principles provide a conceptual framework to ensure that the curriculum content, teaching strategies, learning styles and assessment procedures are properly aligned and fully understood by both the instructors and students to achieve high quality learning outcomes. An action research approach was used during the pilot and trail phases of the research to monitor the implementation of the model and evaluate its effectiveness using mixed methods. The planned two–phase action evaluation used a questionnaire to investigate the effectiveness of knowledge and skill transfer to students, and tutors’ learning progress; in-depth semi-structured interviews were used to survey, interpret and evaluate students’ and tutors’ perceptions of the new teaching and learning approach. Most respondents had a Confucian Heritage Cultural Background. For the first time, the research provides new insights into ways in which Confucian Heritage Cultural factors, interact with constructive principles in developing peer-tutoring methods in a university setting inMacau, and more widely
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Relationship marketing in retail banking in Macau - Wong, Kuai Leong (University of Saint Joseph, 2015)
Keywords: Bank management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Responsible Entrepreneurship. How to Write a Business Plan (Chinese-English Version) - Rothlin, Stephan; Myers, T. A; Thompson, M (University of International Business and Economics Press, 2015)

Rethinking special administrative regions Chinese cultural identities and the role of social media: a case study of Macau - Lou, Lai Chu (University of Saint Joseph, 2015)
Hong Kong and Macau were politically reunified with Mainland China in 1997 and 1999, respectively. These two cities culturally originated from Mainland China, but due to their own colonial experiences, the Chinese cultural identities within Hong Kong, Macau, and Mainland China became different. The nature of Chinese cultural identities within Hong Kong and Macau were hybridized, and they have formed their own Chinese cultural identities with their own peculiarities. The Internet is a popular communication medium and it facilitates cultural communication inside and outside of these three places. The high-speed development of modern technology leads to the variety of services that emerge in the Internet, such as discussion forum, Blog, Facebook, Twitter, etc. These new and open spaces serve as a platform for ordinary people to express themselves in different ways. General observations in the Internet reveal that the discussion on Chinese cultural identity among Hong Kong, Macau, and Mainland China exists. The combination of self-identity and reconstruction of self-cultural identity are happening in these differently colonized places. Some local Chinese people in Macau, and Taiwanese in Taiwan, share this kind of experience as well. Meanings in different issues via different symbols are formed and they can be seen from the photos that circulate in the Internet using threads posted in Blogs or discussion forums. All these kinds of images or contexts become symbols of recognizable identities. Internet use, therefore, has facilitated the cultural communication between Hong Kong, Macau, Mainland China, and Taiwan. It has also intensified the enlightenment of Chinese cultural identity, showing and highlighting in effect the remnants of recognizable traits in these territories that were once colonized by different states. In essence, they may arguably have formed heterogeneous Chinese cultural identities. This study presents the uniqueness of the formation of Macau identity in comparison to Hong Kong, and how different it was from Hong Kong after the end of the colonial period. This ‘awakening process’, it is argued, provides a new perspective for understanding the attendant connotations and evaluations of cultural identities, and the different perspectives used to understand how the Internet is reshaping the social world. The reconstruction of cultural identity is a global issue and cultural hybridity is an essential element for reconstruction of self-cultural identity in the postcolonial period. This study employs postcolonial theory, along with observation, in-depth interview and online data collection and content analysis that were adapted during the course of the research, in order to discuss this phenomenon
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Saldanha hydrothermal field: the role of the sediment-cover in the preservation of ore-forming minerals - Dias, Ágata; Barriga, F (Third InterRidge Theoretical Institute: Magmatic and Tectonic Processes and Seabed Resources at Mid-Ocean Ridges. T2-09, 2015)

Set up and testing a secure cloud - Cheang, Son I. (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Information Technology (MIT); University of Saint Joseph

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

The evolution and SWOT analysis of Macao's social security system - Chiang, Lidia (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The financial valuation study of McDonald's, Inc - Ng, Wai Lon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Future of Macau Aviation Industry: A Long-Term Plan & Development Strategies - Xia, Harry (University of Saint Joseph, 2015)

The impact of retail industry of luxury fashion products in Macau's economy - Zhong, Shao Ling (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The lodging sector in Macau: uncompetitive budget accommodation - Iong, Kuok Un (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Macau Forum and China's Soft Power in the Making: Training the Elite of the Development Portuguese Speaking Countries" - Tran, Émilie; Matias, José Carlos (China - An International Journal, 2015)

The perception of psychological counseling services in Macau: the influence of the Chinese culture of "face" - Lai, Chi Shan (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The seminars of the Macao forum: An illustration of China’s soft-power diplomacy towards the Portuguese-speaking countries - Tran, Emilie; Dos Santos, Jose Carlos Matias (China: An International Journal, 2015)
This article reviews the role that the Macao Special Administrative Region (SAR) plays in China’s cultural and public diplomacy through training programmes organised by the Macao Forum and tailored for the elite of the world’s Portuguese-speaking countries (PSCs). It begins with a review of China’s approach to key instruments of its soft-power offensive and strategy towards the developing world, followed by an overview of Beijing’s linkages with each PSC. Formulated as an expression of China’s cultural diplomacy towards the PSCs, the seminars of the Macao Forum serve as a kind of cooperation in which the provider party—rather than delivering tangible goods and services such as food, money, loans or infrastructure—actually offers grey matter in the form of ideas for initiatives in public policies and reforms, in order to foster further economic development and administrative rationalisation. Adding to an intense debate and substantial literature that discuss quantitatively and qualitatively China’s role in and aid provision to Africa, the authors argue that China, through the Macao Forum’s training programmes, courts the developing PSCs by building the capacity of their human capital, targeting in particular those in the public and private sectors who are in a position to implement their ideas.

The tortuous route of the street hawkers in Macao: tales of persistence from the 1950’s to 2015 - Kam, Pui Han (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Towards A New Professionalism For English Language Teachers In China : Changes In Beliefs And Attitudes, And Classroom Practice - Sansom, David William. (University of Saint Joseph, 2015)
This doctoral dissertation focuses on teacher education in the context of experienced tertiary English language teachers in mainland China. It investigates the changes in teachers’ beliefs and attitudes, and in their classroom practice, that result from an external inservice education and training (INSET) course. It follows up subsequent change in teachers’ classroom practice, and in their beliefs and attitudes, in their teaching contexts one year after the INSET course. This dissertation presents a review of the literature in the field of second language teacher education, shifts in research paradigms in the field, and the characterisation of inservice teacher professional development. The nature of teachers’ beliefs and attitudes, and of teachers’ classroom practice, are synthesised from the literature, and are related to research on stages of innovations. Models of change (from beliefs and attitudes to classroom practice, as well as alternative pathways) are discussed, and a conceptualisation of the processes of teacher change in the context of innovations for experienced inservice teachers is proposed. The research presents a case study of one group of teachers attending an INSET course, and uses qualitative data collection, analysis and interpretation. Findings are discussed which provide insight and guidance for INSET provision in the context of experienced teachers, and which add to the research in the field of teacher education in the context of China. The findings suggest that in the complexity of INSET among individual teachers any one model of the process of teacher change may not be applicable, but rather that multiple possible models of change exist for each teacher—in beliefs and attitudes, and in classroom practice—and for each innovation. It is likely that each individual teacher experiences different change models for different innovations during the same INSET course. The significance and implications of the findings are discussed in relation to INSET provision, teacher change, and theories of teacher education and development, as well as the limits of the study, and future research areas suggested
Keywords: Attitudes; Beliefs; China; Classroom Practice; English Teachers; PhD in Education (D-SE); Professionalism; Thesis and Dissertations; University of Saint Joseph

Traditional Chinese medicine versus allopathic treatments: an economic feasiblity study - Videira, Mafalda Raquel da Silva (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Using Collaborative learning and blended learning with Macau undergraduate students inside and outside university classroom - Monteiro, Elisa Pack Jon Fong Rendall (University of Saint Joseph, 2015)
This thesis reports a mixed methods empirical research which included a university-wide survey and action research in form of a quasi-experiment in collaborative blended learning (CBL) with Macau undergraduate students. The intervention embodied the principles of social constructivism and investigated the putative benefits and challenges of CBL. The purpose of the study was to identify how to promote effective CBL in undergraduate students and to increase effective learning, motivation, autonomy, empowerment, and communication. It found that only small improvements to students’ CBL took place over time, and found that the students needed specific instruction, practice and development in how to collaborate, both with and without online learning. Despite being in a world-leading, enriched digital environment, the students were new to collaboration and online learning. Students discovered and appreciated the benefits and challenges to collaboration and CBL largely by doing it. The thesis shows that CBL does not release teachers from their instructional and pedagogical roles; rather they place teachers at the heart of effective practice and improvements. The study underpins the need for explicit training of students in CBL. It identifies several strategies and tools which can be useful to promote effective genuine CBL
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Valuation of discovery communications - Wong, Mei Wan (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Ebay INC - Pong, Pou I. (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Expedia, Inc - Lei, Lou Man (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Las Vegas Sands - Ho, Chi Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Wal-Mart Stores, Inc - Ng, Mei Wa (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Valuation of Wynn resorts, limited - Leong, Teng Hon (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Visions for Education among Chinese and Non-Chinese Student Teachers: Exploring Cultural Differences - Correia, Ana (The International Journal of Diversity in Education, 2015)
Using Habermas’s theory of communicative action, this study explores the educational visions held by a multi-cultural class of students enrolled in a teacher preparation programme set in a culturally and linguistic diverse urban environment with a recent history of colonialism. The purpose of the study was to analyse the educational and teaching visions put forward by student teachers in an essay during the course “Principles of Education,” which took place in the 2013–2014 academic year and to determine whether the variation in respondents’ vision statements was related to the students’ cultural backgrounds. The students’ awareness of the instructor’s grading role may have influenced the content of their vision statements, and thus Habermas’s theory of communicative action was selected as it allows one to focus on both the content and the process of communicative interaction. The current qualitative research presents data from twenty Macau-Chinese and twenty non-Chinese overseas students. Their visions for education and teaching were examined along the lines of culture. The findings revealed that the idealised representations of what education and teaching is, does and symbolise, varies along culture lines. Since urban educational environments are growing culturally diverse, it is recommended that additional attention be given to cultural awareness in teacher education programmes.

Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.

Western Educated Young Entrepreneurs of Macao: An Exploratory Study - Chan, Weng Si (University of Saint Joseph, 2015)
Keywords: Entrepreneurship; Religious aspects; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

What students are saying on Facebook about their schools? - Kio, Su Iong (Webology, 2015)

Work in the visual and performing arts - Rocco, Ron (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

提升澳門文化遺產保護與管理的水平 - Pinheiro, Francisco Vizeu (澳門研究, 2015)

教育治理背景下的本科訊息公開:基於政策証據視覺的分析教育發展研究 (CSSCI) - 孟瀏今 (2015)